The role of adaptive physical education in the family of stroke sur vivors - Khusainova E.R.; Vershinina A.R.; Safin A.F. (Theory and Practice of Physical Culture, 2025)
The purpose of the study: to investigate modern approaches to managing the condition of patients after stroke and to determine the role of physical education in the family circle. Methodology and organization of research. Based on the results of a survey of family members of stroke survivors, we identified the need for the knowledge that will allow us to continue the process of motor rehabilitation initiated in the hospital. A training course on motor recovery of stroke patients has been developed. The course program is intended for use at home with the participation of the patient’s family. The name is "Stroke Recovery School". Research results and conclusions. The course is based on the Bobat concept, includes exercises from the techniques of PFM, Exart and joint gymnastics, as well as clinical recommendations for postural correction, safe movement and verticalization of patients. It is aimed at training relatives of stroke survivors, students and aspiring specialists in physical rehabilitation. The course lasts 10 academic hours (5 classes of 2 hours each), includes lectures and practice with repetition of the material.